Pracovněprávní vztahy z hlediska optimalizace mzdových nákladů - Štercová, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Bakalářská práce se zabývá problematikou pracovněprávních vztahů. Zaměřuje se na optimalizaci mzdových a osobních nákladů, které zaměstnavateli vznikají v souvislosti se vznikem a trváním nového pracovněprávního vztahu. Také se věnuje řešení problému s nedostatečným počtem zaměstnanců. Na základě analytické části budou zaměstnavateli navržena opatření k optimalizaci mzdových nákladů a počtu zaměstnanců.

The bachelor thesis deals with the matters of labour law relations. It focuses on the optimization of wage and personnel costs incurred by employer in connection with the creation and duration of a new employment relationship. It also deals with solving the problem of insufficient number of employees. On the basis of the analytical part, measures to optimize wage costs and the number of employees will be proposed to the employer.
Employment Relationship in Terms of Wage Costs Optimization
Keywords: zaměstnanec; zaměstnavatel; pracovní poměr; optimalizace; mzdové náklady; zaměstnanecké benefity; employee; employer; employment; optimization; wage costs; employee benefits